O adolescente em conflito com a lei na escola - Silva, Lucélia Maria da (2019)
This research investigates adolescents in conflict with the law at school environment, aiming to identify and discuss the main difficulties they find when returning to their studies, promoting a debate about the aspects of this relationship. The theoretical reference is Edgar Morin Complex Thought, through complexity operators, projection-identification complex and human comprehension as a basis to approach the individuals’ school and social contexts, also to think about social stigmas involved in the socio-educational process they are subjugated. By means of a qualitative study, we used the open interview method with ten adolescents, both sexes, going through socio-educational measure in an open environment of assisted freedom at São Bernardo do Campo Socio-educational Service Centre (Case). The results indicated that most of the time the adolescents do not feel themselves belonging to an environment with attitudes that discriminate them, pointing to the need of rethinking the way these individuals are attended at the regular teaching network and about matters beyond the guaranteed right. Different aspects were observed related to the connection between socio-educational measure, school and adolescent in conflict with the law, highlighting the elements involved in the adolescent study (re)insertion, maintenance and continuity, also the acceptance and/or aversion process at school environment. Concluding, this study points to future investigations in socio-educational measures, education and the Right Guarantee System (SGD) context, strengthening these connections, weak before, sometimes ruptured by part of the school team aversion matters, even because of social stigma or judicial determination obligatory. Though, the right to access and permanence in the human person in development condition must be prioritized without any restriction.